Effects of alkalinity on membrane bioreactors for reject water treatment: Performance improvement, fouling mitigation and microbial structures. (December 2015) - Hu, Dalong; Zhou, Zhen; Shen, Xuelian; Wei, Haijuan; Jiang, Lu-Man; Lv, Yan
Highlights: Effects of NaHCO3 on performances of MBR for reject water treatment were studied. Alkalinity addition into MBR enhanced COD and NH4 -N removal efficiencies. NaHCO3 increased EPS in sludge, but reduced EPS adsorption on membrane surface. EPS in MBR for reject water had larger molecular weight than municipal wastewater. NaHCO3 addition converted the microbial structure and enriched nitrifying bacteria. Abstract: Two submerged membrane bioreactors (MBRs) for reject water treatment were operated to investigate effects of sodium bicarbonate (SB) addition on enhancing process performance and mitigating membrane fouling. Results showed that SB addition enhanced average removal efficiencies of COD and NH4 -N by 14.6% and 38.3%, respectively. With SB addition, the extracellular polymeric substances (EPS) content in activated sludge increased, but those in membrane foulants greatly decreased. Gel permeation chromatography analysis demonstrated that EPS in MBRs for reject water treatment had much larger molecular weight (MW) and broader MW distribution than those in MBRs for municipal wastewater treatment. The fouling mitigation by SB was attributed to a deprotonation mechanism reduced EPS adsorption on negatively charged membrane surfaces, and improvement of degradation efficiency of macromolecular organic matters. SB addition into MBRs for reject water treatment increased microbial abundance, enriched nitrifying bacteria, and converted predominant AOB genus from Nitrosomonas to Nitrosospira .